Analisis Kepatuhan Terhadap Regulasi Pada Pembuangan Emisi Industri Pupuk di PT. X - Salsabilah, Dwi Vanesha; Cundaningsih, Nurvita (Jurnal Serambi Engineering, 2025)
This study aims to analyze the level of compliance of PT X in the disposal of industrial emissions with applicable regulations, especially in the fertilizer production sector. The method used is descriptive quantitative approach with data collection through document study and field observation. The source of air pollution at PT X comes from flue gas emissions generated by 3 chimneys with pollutant control in the form of cyclones. Air quality monitoring is carried out every six months, namely in the January-June and July-December periods. The availability of Green Open Space in the company area still has not reached 20% of the total land area. Meanwhile, the results of the Spearman correlation analysis showed an insignificant relationship between the quality of air emissions and ambient air (p-value> 0.05 or 0.054). Overall, the analysis shows that PT X has implemented several operational standards in accordance with the provisions of government regulations. Based on the analysis, PT X has generally complied with environmental regulations related to industrial emissions, with emission and ambient air quality still in accordance with quality standards. So, even though it has implemented appropriate operational standards and emission control, PT. X still needs to improve compliance in the aspect of green space in industrial areas.